THE WORK OF BISHOP SAVA DEČANAC IN THE ECONOMIC DEVELOPMENT OF KRALJEVO AND ITS SURROUNDINGS AT THE END OF THE 19TH AND THE BEGINNING OF THE 20TH CENTURY (Heritage, 2024)
Throughout the 19th century, while the Serbian state was being rebuilt and developed, with the aim of discarding the backward principles ingrained by centuries of slavery, Sava Dečanac, the bishop of the žička diocese, a learned and experienced man, comprehended the significance of this task. He endeavored to contribute to this struggle, issuing two orders and acts from his position to support the strengthening of Serbian peasants and farmers. He actively participated in the formation of agricultural cooperatives and even played a role in establishing a beekeeping cooperative, which significantly contributed to the economic development and modernization of his jurisdiction and beyond. He delivered speeches in which he emphasized the importance of hard work and the necessity for modernizing agricultural equipment. Historical sources indicate that he was successful in his efforts, as agricultural cooperatives saw an increase in their membership, and a beekeeping cooperative was successfully founded.
Keywords: Sava Barać Dečanac, Cooperatives, Agricultural Cooperative, Agriculture, Kraljevo, beekeeping Cooperatives